Congenital Vocal Cord Paralysis and Late-Onset Limb-Girdle Weakness in MuSK–Congenital Myasthenic Syndrome - Marcus V. Pinto; Jacqui-Lyn Saw; Margherita Milone (Frontiers in Neurology, 2019)
A 30-year-old woman with congenital vocal cord paralysis presented for evaluation of fatigable proximal upper limb weakness and difficulty maintaining the neck erect. Neurologic examination showed bilateral asymmetric eyelid ptosis, mild weakness (MRC 4/5), and atrophy of neck extensors and shoulder girdle muscles, whereas lower limb muscle strength was normal. Repetitive nerve stimulation revealed decremental responses in orbicularis oculis and trapezius. Needle electromyography demonstrated myopathic changes in proximal and paraspinal muscles. Acetylcholine receptor and muscle skeletal receptor tyrosine kinase (MuSK) antibodies, creatine kinase (CK), and lactate were negative or normal. Next-generation sequencing detected two heterozygous variants in the MUSK gene. One variant, c.79+2T>G, is a known pathogenic variant, and the other, c.2165T>C (p.V722A), is a novel missense variant, predicted to be pathogenic by in silico analysis. The two variants were proven to be in trans. This case expands the clinical and molecular spectrum of MuSK congenital myasthenic syndromes.